Knowledge of family planning among muslim women of reproductive age in Garissa County - Ahmed, Mumtaz Muhumed; Nyagero, Josephat; Karama, Mohammed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Kenya’s unmet need for family planning (FP) remains high, at 13.9%, despite government efforts to promote FP methods. Challenges persist, especially in rural areas like Garissa County, where contraceptive prevalence is low, at 12.7%. To determine the level of knowledge of FP among Muslim women of reproductive age in Garissa county. Methods: A cross-sectional mixed methods research design focused on Muslim women aged 15-49 in Garissa County. The study involved 187 participants selected through stratified random sampling. A proportionate sample of women was calculated per subcounty. Data collection used semi-structured interviews with selected women and focus group discussions with community health volunteers from seven subcounties. Quantitative data were analyzed using the Statistical Package for Social Sciences through descriptive analysis. Qualitative data was analysed thematically. Results: Eighty-two percent of women were aware of FP, mainly through community health workers (66%). Only 44% attended FP workshops, showing limited interest in education; additionally, only 39% practiced FP. Among those who used FP, 56% had husbands unaware of their usage. Conclusions: There was knowledge of contraceptives and FP methods, largely due to information shared by community health workers and volunteers. Friends and media also spread FP awareness. However, attendance at FP workshops was low and actual use of FP methods was limited. About half of the women's partners were also aware of and supportive of FP.